The Holocaust on trial - Guttenplan, D. D (Norton, 2001)
D.D. Guttenplan's The Holocaust on Trial is a thorough account of a landmark trial in the ongoing controversy over Holocaust denial. In 1977, the publication of Hitler's War by the British historian David Irving caused a stir with its sweeping revisionist claims about the Holocaust. According to Irving, Hitler did not command the murder of millions of European Jews; in fact, he was barely aware that the Holocaust had happened. In 1994, American historian Deborah Lipstadt refuted Irving's findings in Denying the Holocaust. In 2000, Irving sued Lipstadt for libel--in England, where there is no analog to the First Amendment, and libel laws strongly favor plaintiffs. The ensuing trial raised questions about how "history is judged, as well as made." As a journalist, Guttenplan is particularly skilled at drawing sharp character sketches. (For instance, Irving's swaggering success as a wunderkind historian is epitomized by his fancy Mayfair flat and his Rolls Royce.) The author's talent for character sketches shapes his larger perspective on the trial as well. In this book's conclusion, Guttenplan notes the massive number of empirical facts cited as evidence on both sides of the argument, and rues the lack of "witnesses, memories, testimony," which, he argues, is another central and necessary aspect of historical truth.